2008
DOI: 10.1016/j.cub.2008.07.090
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Matrix Rigidity Promotes Invadopodia Activity

Abstract: Summary Invadopodia are actin-rich subcellular protrusions with associated proteases used by cancer cells to degrade extracellular matrix (ECM) [1]. Molecular components of invadopodia include branched actin assembly proteins, membrane trafficking proteins, signaling proteins and transmembrane proteinases[1]. Similar structures exist in nontransformed cells, such as osteoclasts and dendritic cells, but are generally called podosomes and are thought to be more involved in cell-matrix adhesion than invadopodia [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
332
3
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 291 publications
(371 citation statements)
references
References 27 publications
29
332
3
2
Order By: Relevance
“…Src, in particular, seems to be a master switch for invadosome formation (Cortesio et al, 2008;Destaing et al, 2008;Oikawa et al, 2008), and inhibition of Src-family proteins using inhibitors such as PP2 (Linder et al, 2000a) has proven to be a useful tool for their manipulation. FAK and its hematopoietic homolog Pyk2 bind to both β1 and β3 integrins as well as to Src, and have been shown to localize to invadopodia (Alexander et al, 2008) and the ring structure of podosomes (Pfaff and Jurdic, 2001). Interestingly, FAK was found to function upstream of Src as a negative regulator of invadopodium formation in adenocarcinoma cells (Chan et al, 2009).…”
Section: The Cytoskeletal Backbonementioning
confidence: 99%
See 1 more Smart Citation
“…Src, in particular, seems to be a master switch for invadosome formation (Cortesio et al, 2008;Destaing et al, 2008;Oikawa et al, 2008), and inhibition of Src-family proteins using inhibitors such as PP2 (Linder et al, 2000a) has proven to be a useful tool for their manipulation. FAK and its hematopoietic homolog Pyk2 bind to both β1 and β3 integrins as well as to Src, and have been shown to localize to invadopodia (Alexander et al, 2008) and the ring structure of podosomes (Pfaff and Jurdic, 2001). Interestingly, FAK was found to function upstream of Src as a negative regulator of invadopodium formation in adenocarcinoma cells (Chan et al, 2009).…”
Section: The Cytoskeletal Backbonementioning
confidence: 99%
“…Myosin II has been detected around some active invadopodia, but myosin is mostly absent from these structures. Still, invadopodial localization of other proteins involved in mechanotransduction, such as Cas or FAK, is sensitive to myosin inhibition (Alexander et al, 2008). Clearly, this is an area that needs further exploration.…”
Section: Local Contractilitymentioning
confidence: 99%
“…This leaves open the possibility that differences in culture conditions may influence podosome/invadopodia architecture and function. Indeed, a recent article reported that extracellular matrix rigidity influences both the number and activity of invadopodia (Alexander et al, 2008). Our understanding of the protein components of podosomes and invadopodia has deepened in recent years, and we are also beginning to learn the signals that promote the formation and turnover of these structures.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies investigating the effects of the rigidity of the matrix on cell migration, differentiation, and invasion have used 2D cell culture on hydrogel substrates, including Matrigel™ [77], crosslinked gelatin [78], and synthetic hydrogels [79]. Similarly, the invasiveness of cancer cells has been reported to increase with matrix rigidity when cultured on hydrogels [51,52,78,80].…”
Section: Materials For Investigating Mechanotransduction Pathwaysmentioning
confidence: 99%
“…Similarly, the invasiveness of cancer cells has been reported to increase with matrix rigidity when cultured on hydrogels [51,52,78,80]. However, considering that the elastic modulus of hydrogel substrates is generally <100 nN/μm 2 , their applicability to the bone microenvironment, where the modulus of the mineralized extracellular matrix ranges from 17,100,000-28,900,000 nN/μm 2 [50], may be limited.…”
Section: Materials For Investigating Mechanotransduction Pathwaysmentioning
confidence: 99%